2011
DOI: 10.1097/sap.0b013e31821bd4bc
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Prophylactic Anticoagulation, Deep Venous Thrombosis, and Heparin-Induced Thrombocytopenia in 21 Burn Centers in Germany, Austria, and Switzerland

Abstract: Heparin-induced thrombocytopenia (HIT) is a life-threatening complication in intensive care settings. The timely diagnosis and management of HIT are challenging, and the incidences of HIT and deep venous thrombosis (DVT) may be related to prophylactic anticoagulation standards in burn units. We therefore evaluated, using a questionnaire, prophylactic anticoagulation, HIT management, and incidences of DVT and HIT in burn centers located in the German-speaking part of Europe. In the 21 responding burn centers, 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 37 publications
0
7
0
1
Order By: Relevance
“…Recent studies of burn patients who received heparin thromboprophylaxis found the incidence of HIT to be 0% to 1.6%. 26,45,46 In comparison, the frequency of HIT in orthopedic and cardiac surgery patients was reported to be 4.9 and 1.0%, respectively. 45,46 While extensive data strongly support the clinical benefit and cost-effectiveness of routine thromboprophylaxis in trauma, surgical, and medical populations, 41 the adverse association between increased number of transfusions and possible overzealous use of therapeutic anticoagulation in our study raises the question about the risk-benefit ratio of routine anticoagulation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies of burn patients who received heparin thromboprophylaxis found the incidence of HIT to be 0% to 1.6%. 26,45,46 In comparison, the frequency of HIT in orthopedic and cardiac surgery patients was reported to be 4.9 and 1.0%, respectively. 45,46 While extensive data strongly support the clinical benefit and cost-effectiveness of routine thromboprophylaxis in trauma, surgical, and medical populations, 41 the adverse association between increased number of transfusions and possible overzealous use of therapeutic anticoagulation in our study raises the question about the risk-benefit ratio of routine anticoagulation.…”
Section: Discussionmentioning
confidence: 99%
“…26,45,46 In comparison, the frequency of HIT in orthopedic and cardiac surgery patients was reported to be 4.9 and 1.0%, respectively. 45,46 While extensive data strongly support the clinical benefit and cost-effectiveness of routine thromboprophylaxis in trauma, surgical, and medical populations, 41 the adverse association between increased number of transfusions and possible overzealous use of therapeutic anticoagulation in our study raises the question about the risk-benefit ratio of routine anticoagulation. Because it was sometimes difficult or impossible to obtain satisfactory diagnostic radiology studies on patients with renal dysfunction who were suspected of having a PE, a number of patients were initiated on therapeutic anticoagulation with heparin on the basis of clinical suspicion alone.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several reports of failed flap reconstruction attributed to HIT exist in the literature (Table 1) (2,(6)(7)(8). In cases reported by Schleich et (7) and Tremblay et al (6), the venous thrombotic events occurred intraoperatively and postoperatively.…”
Section: Discussionmentioning
confidence: 98%
“…Aufgrund der oben beschriebenen Hyperkoagulabilität durch ein Volumendefizit bei Verbrennungen > 10 % KOF erfolgt die Antikoagulation durch unfraktioniertes oder niedermolekulares Heparin in Standard-Dosierung wie bei unserer Patientin. Dies zeigt ein Vergleich unter deutschsprachigen Verbrennungszentren [15]. Eine Studie von Lin et al untersuchte den Wirkspiegel von niedermolekularen Heparinen (AntiXa-Spiegel) bei Verbrennungspatienten.…”
Section: Abstract ▼unclassified